DIALOGUE AND DIALECTIC BETWEEN ISLAM AND LOCAL CULTURE IN ECONOMICS AS A REPRESENTATION OF INDONESIAN ISLAM - Nur Kholis (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This paper examines dialogue and dialectic between Islam and local culture in economics as a representation of Indonesian Islam. Islamic teachings in Indonesia have particular characters compared to Islamic tradition in some other Muslim countries. According to many researches, Islam in Indonesia is accommodative – Islam which tends to compromise with situation and condition in Indonesia, particularly social-political condition in a certain time. Dialogue and dialectic between Islam and local culture in economic sector as the representation of Indonesian Islam can be seen from many Islamic economic activities in the society. Some of economic activities practiced in Indonesia are : rejection to the practice of riba, implementation of profit sharing.